Design Optimization and Burst Speed Prediction of a Ti2AlNb Blisk - Yue Guo; Yi-xiong Liu; Yun-wu Wu; Hang Cao; Da Mo (International Journal of Aerospace Engineering)
The increasing demand for power, fuel efficiency, and safety of aeroengines has called for weight reduction and structural integrity examination of the critical components. This paper is aimed at performing a systematic investigation on the design of a high-speed Ti2AlNb blisk, including disc geometry optimization and burst speed prediction. Incorporating the design of the experimental approach and the commercial software has guaranteed that the optimization could be accomplished. Six key parameters were defined as variables with regard to the geometric dimensions whereas the safety factors were set as constraints to make the disc feasible. Sensitivity analysis has been conducted to study the effects of the variables on the safety factors and disc weight. Bore width, web width, and bore angle are identified to be the dominant factors regarding optimization. Results reveal that the bore width and web width are positively related to the safety factors at the cost of increasing the disc weight. On the contrary, the effects of the bore angle show the opposite trend. Finally, the achieved minimum disc weight is 15.2 kg with all the safety factors meeting the requirements. Upon completing the disc shape optimization, the burst speed was estimated using three elaborated methods. The comparisons between the numerical results and the experimental results indicate that the mean stress method is accurate when the correction coefficient is chosen properly. The local stress and strain method and the global plastic instability method also offer a precise prediction on the burst speed with errors of less than 5%. It could also be concluded that the predicted web failure in the radial direction of the disc is in good agreement with the experimental results.